Does genre make a difference? Classical orchestra/popular band musicians' motivation, self-efficacy, and practice experiences' effects on deliberate practice. (January 2023) - Schmidt, Simon; Gruber, Hans
This study investigates the motivational conditions, self-efficacy beliefs, and practice of classical (symphonic, wind) orchestra/popular (rock, pop) band musicians. It thus complements previous research which has shed light on individual aspects of music learning. In both individual and collective work, high quality practice performed in a sufficient amount of time was shown to be very effortful. A mixed-method approach combined a questionnaire and an additional prototypical case interview for each genre with professional musicians. The results show that classical musicians were younger than popular musicians when they started to learn their first and main music instrument and entered their first orchestra or band. While it was confirmed that individual experience was crucial for the time invested in and the quality of deliberate practice, collective practice experiences were also indicated to be a determinant. Furthermore, individual and collective practice were shown to be interrelated. Professional level was suggested to be a more discriminating factor with regard to the variables studied than genre, as professional musicians from both genres deploy deliberate practice strategies in an individual and in a collective context. Improvisation and jamming, however, only appeared in the popular collective and classical individual practice context.